Implementation of Quality Management tools with CP and CPK to reduce defects in the production of metal folders. - Sarmiento Zegarra, Mariana Dalila; Velásquez Arce, Merly Vanessa; Quispe Vásquez, Luis Roberto (LACCEI, 2025)
This study aims to implement quality management tools, specifically Cp and Cpk indices, to reduce defects in the production of metal folders at BAUR METALMIN S.A.C. in Cajamarca, Peru. Issues such as process variability, lack of standardization, and limited quality control were identified, leading to high levels of defective products and economic losses. Tools like the Ishikawa diagram, Pareto analysis, FMEA, and Six Sigma’s DMAIC cycle were applied to improve the production process. Initially out-of-spec Cp and Cpk indices improved after implementing changes in maintenance, training, and workflow, reaching values above 1.0. This approach also reduced costs related to rework and waste, strengthening the company’s quality culture. The proposed model is replicable for other metalworking companies.